Implementasi Teori Belajar Behavioristik B.F. Skinner Dalam Pembelajaran Aqidah Akhlak Di Madrasah Ibtidaiyah - Nur Ichda Kayisa; Risnawita Suminta, Rini; Nadhirroh Fatma Yuthi, Salma (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Aqidah Akhlak education, which is an integral part of Islamic Religious Education, plays a crucial role in shaping students' character and morals. However, its implementation in the field often fails to instill these values in a sustainable and relevant manner in everyday life. Academic concerns arise due to the tendency of learning models that focus more on cognitive understanding, while the affective (attitudes) and psychomotor (skills) aspects that are the essence of Aqidah Akhlak learning are less considered. This study aims to examine the application of B.F. Skinner's behavioristic learning theory in learning Aqidah Akhlak at MI Miftahul Huda Pace Nganjuk, as well as its influence on the learning process and changes in student behavior. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The results showed that the use of positive reinforcement such as praise, achievement stars, and negative reinforcement in the form of task reduction can form good habits, increase learning motivation, and strengthen students' Islamic character. However, challenges were found in the form of students' dependence on rewards and the lack of in-depth reflection on values. Nevertheless, challenges were found in the form of students' dependence on rewards and lack of in-depth reflection on values. The implications of this study show the importance of Aqidah Akhlak learning design that does not only rely on stimulus and response, but also encourages value awareness internally and sustainably.